The Deming System of Profound Knowledge - Reddie, Balaji S. (Journal of Engineering Education Transformations, 2007)
Dr. W. Edwards Deming passed away on the 20th of December 1993 after leading a long and fruitful life. He was best known for catalysing one of the greatest ever industrial turnarounds in history - namely the resurgence of Japan in 1950.